Emergency Neuroanesthesia for Spontaneous Subdural Hematoma in a Pediatric Patient with Hemophilia A: A Protocol-Based Multidisciplinary Approach - Sulistiyawati; Buyung Hartiyo Laksono; Eko Nofiyanto; Dewi Arum Sawitri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Spontaneous subdural hematoma (SDH) in pediatric patients with Hemophilia A is a rare, life-threatening emergency requiring a delicate balance between hemostatic correction and neuroprotective anesthesia. The mortality rate is high without immediate surgical decompression, yet the surgery itself poses catastrophic bleeding risks. Case presentation: We report the case of an 11-year-old male (25 kg) with severe Hemophilia A (Factor VIII <1%) who presented with a three-day history of headache and vomiting, culminating in a sudden loss of consciousness (GCS E2V2M5). Neuroimaging revealed a massive left frontotemporoparietal SDH (8 mm thickness) with a 12 mm midline shift and non-communicating hydrocephalus. The patient had discontinued prophylaxis five months prior. Management involved a strict multidisciplinary protocol. Preoperatively, aggressive Factor VIII replacement was initiated to achieve 100% activity. Intraoperatively, a total intravenous anesthesia (TIVA) strategy utilizing propofol, fentanyl, and dexmedetomidine was employed to maintain cerebral perfusion pressure (CPP) while strictly controlling intracranial pressure (ICP). Tranexamic acid was used as an adjunct. The patient underwent successful craniotomy and hematoma evacuation with minimal blood loss. Postoperative care focused on serial factor VIII replacement and neurological monitoring, resulting in a favorable discharge outcome. Conclusion: Successful management of spontaneous SDH in hemophilia requires a target-controlled approach to both hemostasis and hemodynamics. The integration of preoperative factor loading, neuroprotective anesthesia with dexmedetomidine, and postoperative vigilance is critical for survival.